In search of Chinese democracy : - Fung, Edmund S. K. (Cambridge University Press, 2000)
Edmund Fung examines an important phase of development in China's long quest for democracy. The momentum for democracy, he contends, grew strongest between 1929 and 1949 through civil opposition to the one-party rule of the Guomindang. The Nationalist era contained the germs of a reformist, liberal order, the legacy of which can be seen in the pro-democracy movement of the post-Mao period. This book fills an important gap in the historical literature on Chinese intellectuals between May Fourth radicalism and the Chinese Communists' accession to power.